PLANNING OF MICRO HYDRO POWER GENERATOR LAMPE APE, KONAWE, SOUTHEAST SULAWESI - SANTIAMI (NIM : 15011149), GERRY
Energy needs currently dominated by non-renewable energy sources, but now the usage of renewable energy sources began to develop as the solution. One of the renewable energy that is widely used is water resources. Hydrological cycle of water resources can be used as a source of renewable energy that can be used continuously. This final project describes the planning of small-scale power plant or Micro Hydro Power Generator (Pembangkit Listrik Tenaga Mikro Hidro, PLTMH) in the area Lampe Ape, Konawe, Southeast Sulawesi. Hydrological calculations are done using rational method given that, based on the analysis performed, the power plant watershed is small (<10 km2). Water building design is done with reference to KP Irigasi and some other reference books on small-scale power generator. Based on the topographic map of the area around the planning location, this area has a good potential due to the area being quite hilly. Data used in the calculation is the SRTM rain data, topographic maps (from survey), and the hypothetical data based on the tendency of the area. Mainstay discharge used in the design is Q60 with flood discharge return period of 100 years. Both discharge data were used to design the waterworks at PLTMH. The calculation results are as follows. The height of crest 1.5 m with the width of 14.2 m and the width of bearer channel is 0.9 m with the height, by cross-section, of 0.45 m. The slope of the carrier channel is designed as small as possible in order to reduce head loss. Sluice pond is designed for dewatering every 14 days. The length of mud pool is 16 m with the width and depth of 1 m. Head pond’s dimension is 6.3 m x 2.1 m with a depth of 3.37 m. Pennstock‘s diameter is 0.36 m with the thickness of plate of 5 mm. Pennstock‘s size is selected in order to obtain the smallest speed value so that head loss can be reduced. Waterworks calculation data that has been obtained is then used to perform financial analysis by multiplying the volume of work with the current price of the work. Financial analysis method used is B/C ratio, BEP, and IRR. Based on the financial analysis, the construction project is feasible.